FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES PSIKOSOSIAL LANSIA DI PANTI SOSIAL TRESNA WERDHA ILOMATA KOTA GORONTALO - MANABUNG, DORTJE (JURNAL HEALTH AND SPORT, 2012)
The research was aimed to analysis factor related psikhosocial stress with parenthood in social residence Tresna Werda Ilomata of Gorontalo city. Descriptive method with approach analytic was used in this research. Amount of respondents counted 30 people as parenthood in social residence. The results showed that factor affraid overtaken by death not of caused of psikhosocial stress but more high than family support for parenthood making small psikhosocial stress. Whereas expelled feeling have surround psikhosocial stress.